Ionic liquid/poly-l-cysteine composite deposited on flexible and hierarchical porous laser-engraved graphene electrode for high-performance electrochemical analysis of lead ion. (1st February 2019) - Lu, Zhiwei; Lin, Xueni; Zhang, Junjun; Dai, Wanlin; Liu, Baichen; Mo, Guangquan; Ye, Jiaping; Ye, Jianshan
Abstract: This work reports the manufacture of miniaturized, flexible electrochemical sensors by using a direct laser engraving process that transforms commercial polyimide (PI) films into a laser-engraved graphene electrode (LEGE). The activation procedure was verified to be necessary in substantially enhancing electrochemical performance. The micro-patterned LEGE with porous 3D morphology can form poly-(l -cysteine) (PLC)-modified LEGE (PLC/LEGE) by the in situ electrochemical polymerization of l -cysteine. The PLC/LEGEs were further decorated with ionic liquid (IL). The combination of the enlarged specific surface area of LEGE and the specific complexing ability of PLC, as well as the good conductivity of IL, endowed the newly designed IL/PLC/LESE with abundant active sites, a large active surface area, and fast electron-transfer ability. Thus, the IL/PLC/LESE can act as an electrochemical sensor for lead ions, as revealed by square wave anodic stripping voltammetry (SWASV). Impressively, a wide linear response within the Pb 2+ concentration range of 1–180 μg L −1 and an ultralow detection limit of 0.17 μg L −1  (S/N = 3) for Pb 2+ were obtained. The developed sensor also displayed excellent repeatability, stability, reproducibility, and reliability. Finally, the prepared IL/PLC/LESE-based sensor platform was successfully used to determine real water samples, and results were satisfactory. Graphical abstract: A novel miniaturized and micro-patterned ionic liquid/Poly-(l -cysteine)/laser engraved graphene electrochemical sensor was prepared and sensitive assays of Pb 2+ by square wave anodic stripping voltammetry (SWASV). Image 1 Highlights: Micro-patterned flexible conductive LEGE films were facile prepared by laser engraved process on PI sheet. Newly designed miniaturized and micro-patterned IL/PLC/LES sensor was successfully fabricated. Selective and sensitive electrochemical sensors for the detection of Pb 2+ .